'Also, I Am Sending You Two Cheeses': Dutch Strangers, c. 1470–c. 1550. (4th May 2021) - Levelt, Sjoerd
ABSTRACT: The coming of the Dutch Strangers, religious refugees from the Southern Netherlands, to various cities in England – specifically London and Norwich – in the middle of the sixteenth century, is a new stage in the history of the presence of Dutch speakers in Britain; Dutch-speaking churches were founded, and printers in England became involved in printing Dutch texts. The ease with which these new communities established themselves, however, depended on a pre-existing presence of communities of Dutch speakers, and a long history of Anglo-Dutch cultural, mercantile and political interactions. This paper examines evidence for the existence in the late fifteenth and early sixteenth century of an Anglo-Dutch infrastructure along which people moved, and on which communities were built